y = 7 − 0 . 6 9 x 6 x + 9 + 0 . 6 9 x − 7 6 x + 9 + 6 9
Let x and y be real numbers satisfying the equation above. Find the value of y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice one! (+1)! In the place
−
∞
,
−
2
3
]
∪
(
6
9
7
0
0
,
∞
)
can you put the LaTeX code
\left
in front of ( and LaTeX
\right
in front of ] and ) it makes it look good :)
Log in to reply
Done. Thanks for the suggestion
There's a shortcut. Check out my solution. @Hung Woei Neoh
Since both 7 − 0 . 6 9 x 6 x + 9 and 0 . 6 9 x − 7 6 x + 9 are nested under square roots, both are ≥ 0 . WLOG suppose 6 x + 9 ≥ 0 . For 7 − 0 . 6 9 x 6 x + 9 ≥ 0 , 7 − 0 . 6 9 x ≥ 0 . But this implies 0 . 6 9 x − 7 ≤ 0 ⟹ 0 . 6 9 x − 7 6 x + 9 ≤ 0 . But 0 . 6 9 x − 7 6 x + 9 ≥ 0 since it is nested under a square root. Hence, both 7 − 0 . 6 9 x 6 x + 9 and 0 . 6 9 x − 7 6 x + 9 are equal to 0 , and our desired answer is 0 + 0 + 6 9 = 6 9 .
Well, this is a simpler way
Problem Loading...
Note Loading...
Set Loading...
The trick here is to find out what is the range of values that x can take.
For y to be a real number, the expressions within the square roots must be non-negative, that is:
7 − 0 . 6 9 x 6 x + 9 ≥ 0 and 0 . 6 9 x − 7 6 x + 9 ≥ 0
Now, let's solve it one by one.
For the left square root, let:
6 x + 9 ≥ 0 ⟹ x ≥ − 2 3 7 − 0 . 6 9 x > 0 ⟹ x < 6 9 7 0 0
Draw a number line or a table, and you will get that:
⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ x < − 2 3 − 2 3 ≤ x < 6 9 7 0 0 x > 6 9 7 0 0 7 − 0 . 6 9 x 6 x + 9 < 0 7 − 0 . 6 9 x 6 x + 9 ≥ 0 7 − 0 . 6 9 x 6 x + 9 < 0
Therefore, the range of values of x for the left square root is − 2 3 ≤ x < 6 9 7 0 0 or [ − 2 3 , 6 9 7 0 0 ) , whichever notation you prefer.
Repeat the same steps for the right square root (try it yourself!), and you should get x ≤ − 2 3 , x > 6 9 7 0 0 or ( − ∞ , − 2 3 ] ∪ ( 6 9 7 0 0 , ∞ ) .
Now, what we need is values of x that satisfies both ranges above. From these two ranges, we know that there is only one single exact value of x that satisfies both ranges: x = − 2 3
Therefore,
y = 7 − 0 . 6 9 ( − 2 3 ) 6 ( − 2 3 ) + 9 + 0 . 6 9 ( − 2 3 ) − 7 6 ( − 2 3 ) + 9 + 6 9 = 0 + 0 + 6 9 = 6 9